The new eco-architecture : alternatives from the Modern Movement - Porteous, Colin (London, New York : Routledge, 2009)
The New Eco-Architecture builds a historic bridge between architectural science and theory and design. Colin Porteous explores a range of issues for students and practitioners engaged with the built environment.
boek